If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -18w + -17 = 19 + -20w Reorder the terms: -17 + -18w = 19 + -20w Solving -17 + -18w = 19 + -20w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '20w' to each side of the equation. -17 + -18w + 20w = 19 + -20w + 20w Combine like terms: -18w + 20w = 2w -17 + 2w = 19 + -20w + 20w Combine like terms: -20w + 20w = 0 -17 + 2w = 19 + 0 -17 + 2w = 19 Add '17' to each side of the equation. -17 + 17 + 2w = 19 + 17 Combine like terms: -17 + 17 = 0 0 + 2w = 19 + 17 2w = 19 + 17 Combine like terms: 19 + 17 = 36 2w = 36 Divide each side by '2'. w = 18 Simplifying w = 18
| 7x-2=5x-3+2x-1 | | -2*10-3y=-7 | | 17=3x-2(x-5) | | 2p+2p-3=2p+1 | | -20-6k=-k | | 3x-x+2=22 | | 2x^(1/2) | | 27=y/3-13 | | -2*3-3y=-7 | | 4w-22=8w-70 | | 4x+8x^2=9 | | -17g-4=14-8g | | log(45/x)=0.34 | | -96=-6g+2g | | -2*4-3y=-7 | | 2x-24x=-72 | | -8h+10=-9h+18 | | p^2-2p=-1 | | -9f-6f=24 | | -2*2-3y=-7 | | X^5=65 | | 6=v+5v | | 48=5y-12 | | -3-4z=-15 | | 9x-6=12x-3x | | 3(-2x-1)=2x+5 | | 4(1+5g)= | | 4x+12+2x= | | 4(1+5g)=Submit | | (5x-2)+(2x+8)+90=180 | | 11j-6j+4j=18 | | 7(4p+1)= |